2020
DOI: 10.1002/mgg3.1453
|View full text |Cite
|
Sign up to set email alerts
|

Mutational burden and potential oligogenic model of TBX6‐mediated genes in congenital scoliosis

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Wallin et al's study suggested that mice with PAX1 gene defect exhibited signs of vertebral body and disc loss and ultimately CSD [ 16 ]. Generally speaking, TBX-6 is associated with segmented CS, while LMXIA is related to dysplastic CS [ 17 ]. These data indicate the differential gene expression in different types of CS.…”
Section: Introductionmentioning
confidence: 99%
“…Wallin et al's study suggested that mice with PAX1 gene defect exhibited signs of vertebral body and disc loss and ultimately CSD [ 16 ]. Generally speaking, TBX-6 is associated with segmented CS, while LMXIA is related to dysplastic CS [ 17 ]. These data indicate the differential gene expression in different types of CS.…”
Section: Introductionmentioning
confidence: 99%
“…As a multifactorial disease with a prevalence of ~1/1000 live births [1,7], genetic perturbations, gene-environment interactions, and epigenetic changes are suspected to play a role in the etiology of CVMs [4,8]. Previously, we have reported the mutational burden and potential oligogenic models underpinning CVM development, as well as compound heterozygous inheritance model in TBX6-associated congenital scoliosis (TACS) [9,25,26]. The combined effect of deleterious variants in multiple genes might synergistically lead to the development of the malformations, which gives insight into the complex diseasecausing model of CVMs.…”
Section: Discussionmentioning
confidence: 99%
“…Classical Homocystinuria (OMIM # 236200) is a rare autosomal recessive disorder (incidence between 1/335,000 and 1/200,000) of the methionine metabolism, manifesting with an abnormal accumulation of total homocysteine in the blood, increased excretion of homocysteine in urine, an elevated methionine blood concentration along with a decrease in plasma cystathionine. The genetic defect is in the cystathionine beta-synthase gene ( CBS ), resulting in a deficiency of cystathionine synthetase enzyme activity [ 94 ]. The clinical features of untreated homocystinuria usually manifest in the first or second decade of life and include myopia, ectopia lentis, mitral valve prolapse, accelerated skeletal growth, osteoporosis, skeletal anomalies resembling MFS (body habitus, pectus deformity, kyphoscoliosis, hernias), thromboembolic events and variable intellectual disability.…”
Section: Genetically Related Disorders In Mfs Differential Diagnosismentioning
confidence: 99%